Design and Testing a Neutrons and Gamma-Rays Multilayer Shield Using Different Groups of Cross – Sections (Baghdad Science Journal, 2025)
A preventing shield for neutrons and gamma rays was designed using alternate layers of water and iron with pre-fixed dimensions in order to study the possibility of attenuating both neutrons and gamma-rays.ANISN CODE was prepared and adapted for the shield calculation using radiation doses calculation: Two groups of cross-section were used for each of neutrons and gamma-rays that rely on the one – dimensional transport equation using discrete ordinate's method, and through transforming cross-section values to values that are independent on the number of groups. The memory size required for the applied code was reduced and the results obtained were in agreement with those of standard acceptable document samples of cross –section, this assists the possibility of using this program for calculation of shields and adopting the shield design shield in this research for shielding from neutron and gamma-rays because the calculation of this designed proved the possibility of efficient attenuation of both of these kinds of radiations through from this theoritical study.